A taxonomic revision of the genus Primnoisis Studer [& Wright], 1887 (Coelenterata: Octocorallia: Isididae) using morphological and molecular data - Moore, Kirrily; Alderslade, Philip; Miller, Karen (Zootaxa, 2016)
A complete taxonomic revision of the genus Primnoisis (Isididae) is presented herein, based on original type material of all nominal species and additional specimens from deep-water surveys in sub-temperate and Antarctic waters. A multi-disciplinary approach was used combining morphological characteristics such as colonial branching patterns, polyp structure, sclerite form and arrangement, together with phylogenetic reconstructions using two mitochondrial gene regions (mtMutS and igr1–cox1). The genus Primnoisis is retained with 7 of the 8 nominal species validated (P. antarctica Wright & Studer, 1889, P. rigida Wright & Studer, 1889, P. ambigua Wright & Studer, 1889, P. delicatula Hickson, 1907, P. fragilis Kükenthal, 1912, P. formosa Gravier, 1913 and P. mimas Bayer & Stefani, 1987), with the eighth (P. sparsa Wright & Studer, 1889), synonymised with P. antarctica. In addition, the species Mopsea gracilis Gravier, 1913 is reassigned to Primnoisis and an additional five new species are described (P. chatham n. sp., P. erymna n. sp., P. millerae n. sp., P. niwa n. sp. and P. tasmani n. sp). Most of the species fell into two clear groups, defined both by morphology and genetic grouping, for which two new sub-genera are proposed (P. (Primnoisis) n. subg. and P. (Delicatisis) n. subg.). Three species, P. ambigua, P. mimas and P. tasmani, could not be placed reliably in either sub-genus due to distinctive morphological features or genetic dissimilarity. It was not possible to confirm the monophyly of the genus due to unresolved relationships with the closely related genus Notisis Gravier, 1913 and an undescribed genus of Mopseinae.